Cash plus care: social protection cumulatively mitigates HIV-risk behaviour among adolescents in South Africa - Cluver, L.; Orkin, M.; Boyes, Mark; Sherr, L. (Lippincott Williams and Wilkins, 2014)
Objectives: It is not known whether cumulative ‘cash plus care’ interventions can reduce adolescent HIV-infection risks in sub-Saharan Africa. This study investigated whether parental AIDS and other environmental adversities increase adolescent HIV risk behaviour and whether social protection provision of ‘cash’ or integrated ‘cash plus care’ reduces HIV-risk behaviour. Design: A prospective observational study with random sampling (<2.5% baseline refusal, 1-year follow-up, 96.8% retention).Methods: Three thousand five hundred and fifteen 10–18 year-olds (56.7% girls) were interviewed in South Africa between 2009–2010 and 2011–2012. All homes with a resident adolescent were sampled, within randomly selected census areas in two urban and two rural districts in two provinces. Measures included potential environmental risks (e.g. parental HIV/AIDS, poverty), social protection: receipt of cash/food support (e.g. child grants, school feeding), care (e.g. positive parenting) and HIV-risk behaviours (e.g. unprotected sex). Analyses used logistic regression.Results: Cash alone was associated with reduced HIV risk for girls [odds ratio (OR) 0.63; 95% confidence interval (95% CI) 0.44–0.91, P = 0.02] but not for boys. Integrated cash plus care was associated with halved HIV-risk behaviour incidence for both sexes (girls OR 0.55; 95% CI 0.35–0.85, P = 0.007; boys OR 0.50; 95% CI 0.31–0.82, P = 0.005), compared with no support and controlling for confounders. Follow-up HIV-risk behaviour was reduced from 41 to 15% for girls and from 42 to 17% for boys. Girls in AIDS-affected families and informal-dwelling boys had higher HIV-risk behaviour, but were less likely to access integrated social protection. Conclusion: Integrated cash plus care reduces male and female adolescent HIV-risk behaviours. Increasing adolescent access to social protection may be an effective HIV prevention strategy in Sub-Saharan Africa.